Pertanggungjawaban Pidana Pelaku Black Campaign di Media Sosial Dalam Penyelenggaraan Pemilihan Umum 2024 - Mughniy Arnita (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Election campaigns are activities of election participants or other parties appointed by election participants to convince voters by offering the vision, mission, programme and/or self-image of election participants. In the practice of implementing election campaigns, there are campaign behaviors that harm other parties which are classified as black campaigns. This research is to find out the regulation of black campaigns in Indonesia and criminal liability for perpetrators of black campaigns on social media in the 2024 elections. This researcher uses normative legal research methods and a statute approach and case approach. The results of this study are that black campaigns are regulated in the Criminal Code articles 310 and 311 of the Criminal Code which regulate insults and defamation. in law number 1 of 2023 concerning the Criminal Code in article 263 paragraph 2 regarding broadcasting or disseminating false news or notifications and article 433 paragraph 1 and paragraph 2 regarding attacks on honor / defamation and the law on general elections in article 280 letter c jo 521 regarding prohibitions in campaigns and in the Law on information transactions and electronics in articles 27, 28, 45 and 45 A regarding the prohibition of insults and / or defamation. The criminal responsibility of the perpetrators of black campaigns is that if the elements of guilt can be proven, then they are liable to imprisonment and / or fines.